المعوقات الإدارية للإصلاح الضريبي في سورية - الضابط, مدين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims to improve tax administration in Syria through a stand on the most important administrative obstacles which prevent the application of a clear methodology for administrative reform, and propose appropriate solutions, in light of a set of basic Determinants as have been drawn from previous studies, and the experiences of many countries. For this purpose, it has been to rely on research tools such as personal observation and interviews, which included many of the workers in the tax administration and taxpayers alike. The results of this research have shown that the Syrian tax administration has non capability to carry out the tax reform because of a series of obstacles are classified into two types: external constraints (environmental) and internal constraints (subjective). In light of the foregoing, the study concluded a set of recommendations that make the tax administration through which to meet the requirements of this reform If it have been applied. يهدف هذا البحث إلى تحسين الإدارة الضريبية في سورية من خلال الوقوف على أهم المعوقات الإدارية التي تحول دون تطبيق منهجية واضحة للإصلاح الإداري، واقتراح الحلول المناسبة، في ضوء مجموعة من المحددات الأساسية كما تمً استخلاصها من الدراسات السابقة، وتجارب العديد من الدول في هذا المجال. وقد تم الاعتماد على أدوات بحثية كالملاحظة والمقابلات الشخصية، والتي شملت العديد من العاملين في الإدارة الضريبية، والمكلفين بالضريبة على حد سواء. وقد أظهرت نتائج هذا البحث عدم قدرة الإدارة الضريبية في سورية على القيام بالإصلاح الضريبي حالياً بسبب مجموعة من المعوقات صنفت إلى نوعين: معوقات خارجية (بيئية)، ومعوقات داخلية (ذاتية). وفي ضوء ما سبق، خلصت الدراسة إلى مجموعة من التوصيات التي يمكن للإدارة الضريبية في حال تطبيقها أن تلبي متطلبات هذا الإصلاح.